Integrated Marketing Communication Strategy for Getting Banking Achievements Post the Crisis Issue - Mualima Nuralam; Ign. Agung Satyawan; Ismi Dwi Astuti (PT FORMOSA CENDEKIA GLOBAL, 2023)
In 2020, there were rumors that hit Bank Bukopin, one of which was a crisis rumor. An integrated marketing communication strategy carried out by pensioner credit marketing to get new debtors after the crisis issue. Retirement credit marketing performs various marketing communication mixes, including ; Advertising, Sales Promotion, Events And Experiences, Public Relations And Publicity, Direct Marketing, Interactive Marketing and Personal Selling in this case the author uses a qualitative methodology. Integrated Marketing Communication strategy can generate many benefits both in terms of managing relationships and customer attitudes in the form of loyalty even if a company is affected by a crisis.